2015
DOI: 10.1109/tase.2013.2274517
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Flexible Job Shop Scheduling Using Memetic Algorithms

Abstract: In this paper, we propose new memetic algorithms (MAs) for the multiobjective flexible job shop scheduling problem (MO-FJSP) with the objectives to minimize the makespan, total workload, and critical workload. The problem is addressed in a Pareto manner, which aims to search for a set of Pareto optimal solutions. First, by using well-designed chromosome encoding/decoding scheme and genetic operators, the nondominated sorting genetic algorithm II (NSGA-II) is adapted for the MO-FJSP. Then, our MAs are developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(84 citation statements)
references
References 58 publications
1
83
0
Order By: Relevance
“…, , 푘 ∈ cor }, which contains ∑ 푛 푖=1 cor actions. Now, a hierarchical strategy [27] is adopted to calculate Δ and Δ which, respectively, represent…”
Section: Description Of Local Search Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…, , 푘 ∈ cor }, which contains ∑ 푛 푖=1 cor actions. Now, a hierarchical strategy [27] is adopted to calculate Δ and Δ which, respectively, represent…”
Section: Description Of Local Search Methodmentioning
confidence: 99%
“…With the aim of keeping population diversity, immune and entropy principle were adopted in multiobjective genetic algorithm (MOGA) [25]. Two memetic algorithms (MAs) were, respectively, proposed, both of which integrate nondominated sorting genetic algorithm II (NSGA-II) [6] with effective local search techniques [26,27]. Several effective neighborhood approaches were used in variable neighborhood search to enhance the convergence ability in a hybrid Pareto-based local search (PLS) [28].…”
Section: Related Workmentioning
confidence: 99%
“…Rahmati et al [67] developed non-dominated sorting of EA and non dominated ranking EA for multi-objective PFOSP and he proposed new multi-objective Pareto-based modules and a new measure for the multi-objective evaluation. [42] 2002 FOSP EA + AL Baykasoglu et al [7] 2004 FOSP TS + PDR Xia and Wu [79] 2005 FOSP PSO + SA Gao et al [26] 2006 FOSP EA Gao et al [27] 2007 FOSP EA + BSP Zribi et al [89] 2007 FOSP EA + BBA + LS Gao et al [28] 2008 FOSP EA + VNS Tay and Ho [75] 2008 FOSP EA + PDR Wang et al [76] 2008 FOSP FBS + PDR Zhang et al [87] 2009 FOSP PSO + TS Li et al [50] 2010 FOSP EA + VNS Frutos et al [25] 2010 FOSP EA + SA Wang et al [77] 2010 FOSP EA + AIS Gao et al [30] 2010 FOSP EA + AIS Grobler et al [35] 2010 FOSP PSO + PDR Li et al [48] 2010 FOSP TS + VNS Moradi et al [58] 2011 FOSP EA + PDR Moslehi and Mahnam [59] 2011 FOSP PSO + LS Li et al [49] 2011 FOSP PSO Li et al [47] 2011 FOSP PSO Rajkumar et al [68] 2011 FOSP GRASP Chiang and Lin [17] 2013 FOSP EA Rahmati et al [67] 2013 FOSP Gas Shao et al [72] 2013 FOSP PSO + SA Gao et al [29] 2014 FOSP HSA + LS Jia and Hu [41] 2014 FOSP TS Karthikeyan et al [45] 2014 FOSP DFA + LS Li et al [51] 2014 FOSP PSO + TS Rohaninejad et al [69] 2015 FOSP EA Yuan and Xu [84] 2015 FOSP EA + LS Rohaninejad et al [69] proposed a nonlinear IP model and also the hybridized EA with meta-heuristic, which is a multi-attribute decision making method, for multi-objective PFOSP with machines capacity constraints. The computational results are obtained by well-known multi objective algorithms from the literature showed that the proposed algorithm to obtain throughout better performance, especially in the closeness of the solutions result to the Pareto optimal front.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ho and Tay [6,7] proposed a hybrid evolutionary algorithm with local search, and meanwhile introduced an elitism memory to store all non-dominated solutions that have been found. Yuan and Xu proposed a new memetic algorithms (MAs) by incorporating a local search algorithm into the adapted NSGA-II for MOFJSP [8]. Xia and Wu [9] proposed a hybrid method to solve MOFJSP.…”
Section: Introductionmentioning
confidence: 99%